2022
DOI: 10.1093/plcell/koac210
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear import pathway exploited by pathogenic noncoding RNAs

Abstract: The prevailing view of intracellular RNA trafficking in eukaryotic cells is that RNAs transcribed in the nucleus either stay in the nucleus or cross the nuclear envelope, entering the cytoplasm for function. However, emerging evidence illustrates that numerous functional RNAs move in the reverse direction, from the cytoplasm to the nucleus. The mechanism underlying RNA nuclear import has not been well elucidated. Viroids are single-stranded circular noncoding RNAs that infect plants. Using Nicotiana benthamian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…Previous studies have revealed that S26 is a component of the RY motif, which serves as the binding site for the viroid RNA binding protein (Virp1) [ 49 ]. This protein interacts with IMPORTIN ALPHA-4 to facilitate the nuclear import of PSTVd [ 50 ]. While the role of this stem in the cell-to-cell movement and systemic trafficking of PSTVd remains unclear, our data also suggests its potential involvement in these two processes.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that S26 is a component of the RY motif, which serves as the binding site for the viroid RNA binding protein (Virp1) [ 49 ]. This protein interacts with IMPORTIN ALPHA-4 to facilitate the nuclear import of PSTVd [ 50 ]. While the role of this stem in the cell-to-cell movement and systemic trafficking of PSTVd remains unclear, our data also suggests its potential involvement in these two processes.…”
Section: Resultsmentioning
confidence: 99%
“…Viroids are now subdivided into the families Pospiviroidae and Avsunviroidae , which are located mainly in the nucleus and the chloroplast, respectively. Their locations also suggest their usage of different replication strategies, host polymerases, structural elements, and trafficking [ 13 , 109 , 110 , 111 ]. The knowledge on viroid-induced symptoms is increasing, but still not solved fully.…”
Section: Discussionmentioning
confidence: 99%
“… Timeline of research development of viroids (green text) [ 4 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], satellite RNAs (orange text) [ 11 , 12 , 45 , 46 , 47 , 48 , 49 ], prions (red text) [ 7 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , …”
Section: Figurementioning
confidence: 99%
“…The exact mechanism leading to the nuclear translocation of circAMOTL1 in wound healing or cardiac repair is also unknown. Interestingly, in viroids-infecting plants, nuclear import is driven by forming a C-loop on the circular RNA, which is recognized by VIRP1 that serves as a scaffold for Importin alpha-4 to mediate nuclear transport [112]. Similar mechanisms involving the formation of particular secondary structures and interactions with adaptor proteins could regulate the intracellular transport of circRNAs.…”
Section: Conclusion and Perspectivementioning
confidence: 99%